The Holy Compound on Mount Sion – An Epigraphic Heraldic Corpus (Part 1): The Walls of the Cenacle - Halevi, Shai (Liber annuus, 2024)
In autumn 2021, researchers of the Israeli Antiquities Authority conducted a photographic survey to document all the inscriptions and graffiti on the walls of the Cenacle - the traditional site of the Last Supper taken by Jesus and the Apostles before the Passion. The combination of multi-spectral photography and Reflectance Transformation Imaging (RTI) enabled the rediscovery of several epigraphic elements that were too faded or worn to be seen with an untrained eye. Initially 30 written inscriptions and nine images, including five coats of arms, were identified. Having deciphered and read these, we attempted to link them with concrete historical figures. For the sake of comparison, we also considered several further inscriptions and heraldic elements from other parts of the Holy Compound on Mount Sion. With some notable exceptions, the great majority of the graffiti dates to the period when the Cenacle was the focal point of a Franciscan monastery which served as the original seat of the Custodia Terrae Sanctae. Among the most important and moving discoveries were: an inscription that might allude to the Christmas pilgrimage of King Hetoum II of Cilicia; an autograph of the 15th century German pilgrim author Johannes Poloner; and the coat of arms of the Swiss national hero, Adrian I von Bubenberg. Although not all inscriptions could be related to a concrete person, when considered as a whole, the graffiti assemblage provides valuable evidence of the origin of the pilgrims who visited Mount Sion and the Monastery. These included Armenians, Czechs, Italians, and Serbs. The largest single group, comprising around half of all visitors, were Arabic-speaking Eastern Christians. The Cenacle’s inscriptions are an invaluable reminder of the diversity of the Christian pilgrimage to late medieval Jerusalem.